Implementasi Etika Bisnis Islam dalam Meningkatkan Kesejahteraan Pedagang - Yunita Rahayu; Muhammad Iqbal Fasa; Suharto (Scimadly Publishing, 2022)
A business can lead to a transaction between a seller and a buyer regarding a particular object or item. Islam justifies trade, commerce, and or buying and selling. In Islam, it has also been regulated how to transact correctly, this rule is known as Islamic business ethics. In this study using library research method (library review) which collects data from various kinds of literature, the research aims to find out how the implementation of Islamic business ethics in improving the welfare of cattle traders. Welfare in sharia economy aims to achieve human welfare as a whole, namely material welfare, spiritual and moral welfare. The result of this study is to find out how to implement Islamic business ethics in carrying out a muamalah activity.